Actual problems of legal regulation of medical support and fight against doping in Kazakhstan sport (Journal of actual problems of jurisprudence, 2020)
The article is devoted to the actual problems of legal regulation of medical support and fight against doping in Kazakhstan sport. In addition, the article analyzes the practice of medical support and antidoping in world sports. The purpose of the article is to intensify the fight against doping in Kazakhstan’s sports and medical support of athletes of the country, to identify specific ways to solve these problems. The practical significance of the article is the possibility of using the conclusions and proposals to improve the legislation in the field of sports. The results of the study can be used in the preparation of legal acts of the Ministry of culture and sports of the Republic of Kazakhstan, to improve the work of state bodies in the field of medicine and sports. The methodological basis of the article consists of General scientific and special methods of cognition such as system, logical – legal, historical and specifically sociological. The article reflects the specific ways of solving the problems of medical support of athletes and the fight against doping in sports, which are the most urgent and complex problems of Kazakhstan’s sport. Key words: sports medicine, sports competitions, physical culture and sport, anti-doping struggle, World anti-doping Agency, Kazakhstan sport, rights of athletes.